Customer relationship marketing services provided by Duha Gemilang Enteprises for customers in Melaka / Shahril Mohamed Hanafi (Faculty of Business and Management, 2007)
The purpose of this research is to study the customer relationship marketing services provided by Duha Gemilang Enterprises for customers in Melaka. The objective was to study the significant between customer relationship marketing and customer service, personnel, products and services, and quality. Other than that, this research study was also to measure the level of customer satisfaction of all items that will influence the relationship with the services provided to them. To meet the objectives, interviews, questionnaire and other secondary source such as reports, database and so on are been used for data collection. Based on frequency, cross tabulation and ANOVA test, a clear findings and results are observed. The findings showed that most of the customers were satisfied with the customer relationship provided to them. At the end of the research, based from the findings several recommendations have been made to the firm and also for future research purposes.